Evolution of the dynamic properties of the cortex–basal ganglia network after dopaminergic depletion in rats - Cyril Dejean; Agnes Nadjar; Catherine Le Moine; Bernard Bioulac; Christian E. Gross; Thomas Boraud (Neurobiology of Disease, 2012)
It is well established that parkinsonian syndrome is associated with alterations of neuronal activity temporal pattern basal ganglia (BG). An increase in synchronized oscillations has been observed in different BG nuclei in Parkinson's disease patients as well as animal models such as 6-hydroxydopamine treated rats. We recently demonstrated that this increase in oscillatory synchronization is present during high-voltage spindles (HVS) probably underpinned by the disorganization of cortex–BG interactions. Here we investigated the time course of both oscillatory and motor alterations. For that purpose we performed daily simultaneous recordings of neuronal activity in motor cortex, striatum and substantia nigra pars reticulata (SNr), before and after 6-hydroxydopamine lesion in awake rats. After a brief non-dopamine-specific desynchronization, oscillatory activity first increased during HVS followed by progressive motor impairment and the shortening of SNr activation delay. While the oscillatory firing increase reflects dopaminergic depletion, response alteration in SNr neurons is closely related to motor symptom.